SENTENCE STRUCTURE AND SYNTAX IN OLD ENGLISH - Ergashev Farruxbek Ortiqboy o'g'li, (TADQIQOTLAR, 2025)
Abstract: This paper examines the sentence structure and syntactic organization of  Old  English  as  used  between  the  5th  and  11th  centuries.  Using  a  descriptive-historical  linguistic  approach,  the  study  investigates  how  casebased  morphology, flexible word order, and the absence of rigid syntactic rules shaped clause formation in Old English prose and poetry. Analysis of religious, legal, and poetic texts shows that the  inflectional  system  allowed  variation  such  as  OV  and  VO  patterns,  while subordinating conjunctions and relative markers signaled clause relationships without depending strictly on word position. The results indicate that syntactic flexibility in Old  English  was  structurally  sustained  by  rich  inflection  rather  than  word  order constraints.  Furthermore,  the  coexistence  of  Germanic  syntactic  inheritance  and emerging Latin-influenced constructions reflects a transitional phase that paved the way for Middle English syntactic stabilization. The findings suggest that Old English syntax  represents  a  key  stage  in  the  diachronic  development  of  English  sentence structure,  linking  morphologically  governed  and  positiongoverned  grammatical systems.